The hydro politics of living with urban wetlands in Zimbabwe: pasts, presents and future - Mupani, Helen Tevedzerai (Environmental Humanities, 2026)
Urban wetlands are important ecosystems that support both nature and people, but they are under threat from growing cities, climate change, and economic challenges. This thesis looks at how people interact with wetlands, focusing on the power, policies, and everyday actions that shape how wetlands are used, changed, and cared for over time. It examines the case studies of Borrowdale and Mbare in Harare to discover how communities living alongside wetlands, engage with them, the value they attach to these spaces – social, economic, spiritual, and cultural – and how they are impacted by management policies over time. The research highlights how people have become increasingly disconnected from the natural environment, showing how changes over time – from pre-colonial traditions to colonial rule and modern policies – have reshaped the way people view and use wetlands, by extension how policies get imprinted in landscapes, and how they shift relationships over time. Borrowdale and Mbare tell different stories about who controls wetlands, who benefits from them, and who is left out. Drawing on personal experiences and history to the conversation about wetlands, the aim is to show how focusing only on one field, like conservation, economics, or anthropology, limits how we understand and live with wetlands. Instead, it calls for a broader, more connected way of thinking about these important spaces. In doing so we broaden how we manage and live with wetlands through co-generative and response-able approaches for more habitable futures.